propolis Study of phenols, flavonoids, and antioxidant capacity of two types of propolis in the coastal region. - سلطانة علي (Latakia University Journal -Biological Sciences Series, 2024)
The research was conducted to clarify the importance of propolis, as beekeeping is considered one of the oldest activities practiced by humans in the countries of the Mediterranean Basin, and one of these countries is Syria, due to its moderate climate, diverse plant cover, and many water sources, where this activity has witnessed remarkable development in recent years. Propolis is a mixture of gummy resinous materials that bees collect from the bark of trees and the buds of some plants, and some materials are added to it, such as the salivary and waxy secretions that the bees excrete from their stomachs. The bees use propolis as a structural material to stabilize the wax discs or as a disinfectant for the hive. Therefore, the research aimed to estimate phenolic compounds, determine the content of flavonoids in propolis, and study its antioxidant activity through the DPPH test The results demonstrated that the collected propolis was rich in total phenols, the average amount of which in both species (coastal and mountainous) was 102.57 mg/g, 98.67 mg/g), and the average amount of flavonoids was 74.49 mg/g, 67.83 mg/g. The coastal and mountain type, respectively. As for the value of I% (percentage of free radical inhibition), its highest value was 91.3% in sample B2, followed by sample C1 with a value of 90.4%, and the lowest value was in sample B3 with a value of 77.9%, which makes it a very important material. You should take advantage of its distinctive properties of antioxidant capacity and fighting free radicals.